Deteccion de Phoma exigua var. heteromorpha en viveros de adelfa (Nerium olender L.) en España - Alvarez, L.A.=700 1 Armengol, J.; Perez-Sierra, A.; Leon, M.; Abad-Campos, P.; Vicent, A.; Beltran, C.; Garcia-Jimenez, J.
(En, Es)
ilus., 11 ref.
Keywords: NERIUM OLENDER; PLANTAS ORNAMENTALES; PHOMA EXIGUA; CAIDA DE LAS HOJAS; MANCHAS; ESPAÑA